Development of dna aptamers against bipd antigen of burkholderia pseudomallei for diagnostic applications - Selvam, Kasturi (2025)
Melioidosis is an infectious disease caused by Burkholderia pseudomallei (B. pseudomallei). A major challenge in diagnosing this disease arises from the limitations of the gold standard method, which is often time-consuming and lacks sufficient sensitivity. Therefore, this study aimed to develop DNA aptamers targeting the Burkholderia invasion protein D (BipD) antigen for melioidosis diagnostic applications. The recombinant BipD protein was expressed and purified to serve as the target for DNA aptamer isolation through systematic evolution of ligands by exponential enrichment (SELEX). Three potent aptamers were isolated based on their high frequency. All these selected aptamers were evaluated for their binding affinity to the recombinant BipD protein, followed by specificity testing against lysates from other Gram-negative bacteria, including Salmonella Typhi, Shigella flexneri, Escherichia coli and Klebsiella pneumoniae, through an enzyme-linked oligonucleotide assay (ELONA). AptBipD1 exhibited the highest binding affinity, with a dissociation constant (Kd) of 0.91 ± 0.08 μM, which was lower than AptBipD13 and AptBipD50. All three aptamers demonstrated strong specificity for B. pseudomallei compared to other tested bacteria. Binding analyses were performed through computational methods such as molecular docking and molecular dynamics (MD) simulations. Computational analysis revealed that AptBipD1 exhibited the highest predicted binding free energy of -22.8 kcal/mol and greater stability upon binding with BipD protein, as well as the binding site located away from its 5' and 3' ends. This finding suggests that immobilising this aptamer at either end would not affect its binding characteristics. An electrochemical aptasensor was developed by immobilising the most promising aptamer onto screen-printed gold electrodes. AptBipD1-based electrochemical aptasensor demonstrated high specificity for B. pseudomallei over other bacterial strains. This sensor achieved a limit-of-detection (LoD) of 3.4 ± 0.03 ng/mL and limit-of-quantification (LoQ) of 59.2 ± 0.03 ng/mL in buffer, and a LoD of 3.5 ± 0.06 ng/mL and LoQ of 63.2 ± 0.06 ng/mL in spiked serum. The electrochemical aptasensor developed using AptBipD1, which had high binding affinity and specificity, demonstrated low LoD and LoQ in both buffer solution and serum spiked with protein. This indicates its potential for rapid and accurate detection of the BipD protein, making it suitable for diagnostic purposes in melioidosis